What are you doing on Tinder? Impression management on a matchmaking mobile app. Issue 11 (2nd November 2017) - Ward, Janelle
ABSTRACT: Mobile dating applications such as Tinder have exploded in popularity in recent years. On Tinder, impression management begins with a motivation to download the app, the choice of one's profile photos and an assessment of the expectations of potential Tinder matches. These processes occur in a technologically mediated environment of reduced cues and increased control, local proximity and a reduced filtering process. My focus in this paper is this first stage of impression management, which consists of both impression motivation and impression construction. Specifically, what are the pre-match impression management practices of Tinder users? I present the results of interviews with Tinder users in the Netherlands. Participants were recruited via a Tinder profile that advertised the study using the University emblem and a brief description. Interview questions focused on user understandings of self-presentation practices and profile construction. The interviews also examined how users evaluated their potential matches. Results show users' motivations for using Tinder range from entertainment to ego-boost to relationship seeking, and these motivations sometimes change over time. Profile photos are selected in an attempt to present an ideal yet authentic self, and chosen as an illustration of not only one's desirability but also of other indicators such as education level. Tinder users 'swipe' not only in search of people they like, but also for clues as to how to present themselves in order to attract others like them. This research offers insight into user experiences and perceptions within the still under-researched area of inquiry.